Efektivitas Media Gambar Terhadap Kemampuan Menulis Teks Persuasi pada Siswa Kelas VIII SMP Negeri 11 Lubuklinggau - Komaria, Resi; M. Syahrun Effendi; Sri Murti (Linggau Jurnal Language Education and Literature, 2023)
ABSTRACT This thesis is entitled "The Effectiveness of Image Media on the Ability to Write Persuasive Texts in Class VIII Students of SMP Negeri 11 Lubuklinggau". The research method used in this study is a quasi-experimental method. The population in this study were all students of class VIII, totaling 148 students and the sample in this study was class VIII.4. randomly selected 28 students. Analysis of the data used in this study using the "t" test. based on the results of data analysis that has been carried out with the SPSS Version 20 application, the "t" test data obtained with a value of (12,229) by looking at the Sig (2-tailed) of 0.000 and seen from the confidence level or 0.05 So the Sig (2-tailed) data is smaller than the confidence level (0.000 < 0.05), it can be stated that Ha is accepted and Ho is rejected. Based on these results, it can be concluded that Image Media is Effective for Improving the Ability to Write Persuasive Texts in Class VIII Students of SMP Negeri 11 Lubuklinggau.